2009
DOI: 10.1038/labinvest.2009.39
|View full text |Cite
|
Sign up to set email alerts
|

Transgenic mitochondrial superoxide dismutase and mitochondrially targeted catalase prevent antiretroviral-induced oxidative stress and cardiomyopathy

Abstract: Transgenic mice (TG) were used to define mitochondrial oxidative stress and cardiomyopathy (CM) induced by zidovudine (AZT), an antiretroviral used to treat HIV/AIDS. Genetically engineered mice either depleted or overexpressed mitochondrial superoxide dismutase (SOD2 þ /À KOs and SOD2-OX, respectively) or expressed mitochondrially targeted catalase (mCAT). TGs and wild-type (WT) littermates were treated (oral AZT, 35 days). Cardiac mitochondrial H 2 O 2 , aconitase activity, histology and ultrastructure were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
40
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(43 citation statements)
references
References 55 publications
3
40
0
Order By: Relevance
“…AZT causes cardiac gene expression changes, altered DNA methylation, and changed SAM abundance. These results support and correlate mechanistically with pathophysiological changes of CM that we reported previously (20). In those studies, AZT caused CM to develop in wild-type mice (WT), while MCAT was able to prevent that CM.…”
supporting
confidence: 91%
See 3 more Smart Citations
“…AZT causes cardiac gene expression changes, altered DNA methylation, and changed SAM abundance. These results support and correlate mechanistically with pathophysiological changes of CM that we reported previously (20). In those studies, AZT caused CM to develop in wild-type mice (WT), while MCAT was able to prevent that CM.…”
supporting
confidence: 91%
“…Our previous work identified oxidative stress to be a critical component in the development of CM in AZT-treated mice (20). In those studies, pathophysiological changes in cardiac mass and structure were identified following 35 days of AZT treatment, and these changes could be attenuated or prevented by enhanced ROS scavenging by MCAT (7)(8)(9).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Animal studies using transgenic mice over-expressing mitochondrially-targeted SOD and catalase have already shown the potential of this strategy, since these transgenic mice were associated with significant reductions in cardiac mitochondrial oxidative stress and improvements in left ventricular function after antiretroviral-induced cardiomyopathy (Kohler et al 2009). Indeed, the development of antioxidants that specifically target the matrix-facing inner surface of the mitochondrial membrane is hypothesised to protect against mitochondrial oxidative damage (Ross et al 2005).…”
Section: Mitochondrially-targeted Antioxidantsmentioning
confidence: 99%